HUBUNGAN KONSUMSI PANGAN DAN POLA ASUH MAKAN DENGAN PEMENUHAN GIZI ANAK KELAS V SD SWASTA GKPS 1 DI PEMATANG SIANTAR - Siahaan, Riana Friska; Pasaribu, Sartika (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
ABTRACT This study aims to determine (1) Food Consumption of Primary School Children (2) Fostering Pattern of Elementary School Children (3) Fulfillment of Nutrition of Primary School Children (4) Food Consumption and Foster Patterns with Nutrition of Elementary Children. The population of this study is as many as 40 people taken from class V and all children in the class V age 10-12 years. Recommended Nutrition Adequacy Rate for boys and girls at 10-12 years old is 2050 kcal. Thus the consumption of children's food in private primary GKPS Pematangsiantar has not reached for the whole. Data of change of food consumption (X1) got lowest score 74 and highest score 95. average score (M) = 84,8, Sd = 5,04 and tendency level there are 37,5 percent tends to enough, and 32,5 percent tend less. Data of change of eating pattern (X2) was obtained the lowest score 93 and the highest score 127. average score (M) = 108,23, Sd = 10 and the tendency level there are 27,5 percent tends to enough, and 20 percent tend to less. The equation of regression of nutrient fulfillment (Y) on food consumption (X1) is stated linear and significant at significant level at Î± = 0,05 where linear F count <Ftable (-8,99 <2,29) 232,6 57,4 X1 and Significant F count> Ftable (7.55> 4.00). On the regression equation needs to be tested significance or significance and kelinierannya. The nutritional regression equation (Y) on the feeding pattern (X2) is expressed linear and significant at the significant level at Î± = 0.05 where linear F count <Ftable (-0.08 <2.23) and No Means Fcount> Ftable (0.057 <4.00). Kata Kunci: Konsumsi Pangan, Pola Asuh Makan, Pemenuhan Gizi